Skyddsrum och slagfält: Två polska berättelser om kärleken och samhället - Wolanik Boström, Katarzyna (Kulturella Perspektiv – Svensk etnologisk tidskrift, 1998)
The author tells a story of two well-educated Polish couples. Izabella and Leopold rejected the socialist rhetoric of new gender roles and family ideals. Although the material basis of their life had undergone a fundamental change due to the egalitarian ideology, they sustained an alternative, old-fashioned upper-class lifestyle. Teresa and Marek wanted to be a modern, equal couple, independent of family bonds and old social distinctions. In the long run, however, their ideas of prestige and status, gender roles, goals in life, taste and social behaviour became too incongruent and the mediation too problematic. Stories about love and marriage can be a starting point for analysis of a couple's confrontations with social norms and strata, ideas of femininity and masculinity and changing living conditions in society. The lovers' aspirations of creating a "shared reality" can help them to maintain their own protective space — but the shared life can also turn into a social and normative battleground.